Examining the Online Processing of Satirical Newspaper Headlines. Issue 1 (2nd January 2019) - Skalicky, Stephen; Crossley, Scott A.
ABSTRACT: Previous investigations of satire posit that satire comprehension is influenced by prior knowledge, satirical strategies, and other demographic features, such as age. However, these claims have not yet been tested using online processing techniques. In this study we investigate satire processing using newspaper headlines from the satirical American newspaper The Onion and nonsatirical headlines from The New York Times . Reading times and humor ratings were gathered from 76 participants using behavioral response data. Results demonstrate that a higher age results in significantly higher reading times for satirical compared with nonsatirical headlines. In addition, levels of prior knowledge significantly interacted with different satirical strategies, influencing both reading times and perceptions of humor. Measures of headline familiarity and sincerity also interacted with perceptions of humor and satirical strategy. These results provide additional evidence for the importance that age, prior knowledge, and satirical strategies have on satire comprehension.